Association with Delinquent Peers: Intervention Effects for Youth in the Juvenile Justice System - Leve, Leslie D. (2005)
Although association with delinquent peers is a recognized precursor to ongoing delinquency problems, youth in the juvenile justice system are commonly prescribed intervention services that aggregate delinquent youth. However, little is known about the process variables that mediate the relationship between aggregating youth in intervention settings and poor subsequent outcomes. We examined data from two randomized intervention trials (one male sample and one female sample) with delinquent adolescents placed either in Multidimensional Treatment Foster Care (MTFC) or in group care. Path analyses suggested that the MTFC youth had fewer associations with delinquent peers at 12 months than did the group care youth. Further, associating with delinquent peers during the course of the intervention mediated the relationship between group condition and 12-month delinquent peer association. Implications for the development of interventions with delinquent youth are discussed.